2022
DOI: 10.1039/d1cy01915e
|View full text |Cite
|
Sign up to set email alerts
|

The tendency of supports to generate oxygen vacancies and the catalytic performance of Ni/ZrO2 and Ni/Mg(Al)O in CO2 methanation

Abstract: The Ni/ZrO2, Ni/Mg(Al)O, and Ni/SiO2 catalysts were employed in the CO2 methanation. The catalysts were characterized by XPS, XRF, XRD (Rietveld refinement method), TPR, EPR, BET, CO2+H2-TPSR, CO+H2-TPSR, CO2-TPD, CO-TPD,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…( b ) Selectivity to CH 4 (squares) and CO (triangles) versus temperature. The catalyst colors and the experimental conditions are the same as in ( a ) [ 76 ]. Copyright (2022) Catalysis Science & Technology.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…( b ) Selectivity to CH 4 (squares) and CO (triangles) versus temperature. The catalyst colors and the experimental conditions are the same as in ( a ) [ 76 ]. Copyright (2022) Catalysis Science & Technology.…”
Section: Figurementioning
confidence: 99%
“…Copyright (2021) Fuel.ZrO 2 has abundant active and basic sites on its surface, good thermal stability, and high porosity[64]. Espino et al[76] studied the performance of Ni/ZrO 2 , Ni/Mg(Al)O, and Ni/SiO 2 catalysts in the CO 2 methanation reaction and found that the Ni/ZrO 2 catalyst has the highest CO 2 conversion rate and CH 4 selectivity (98%), as shown in Figure9. Due to the insertion of Ni into the ZrO 2 lattice and its own defects, oxygen vacancy was generated, which improved the adsorption and dissociation of CO on the Ni/ZrO 2 catalyst.CeO 2 has a high specific surface area and abundant oxygen vacancy[77].…”
mentioning
confidence: 99%
“…Surface oxygen vacancies can promote CO 2 adsorption and activation on catalyst surfaces. In recent years, substantial research efforts have focused on developing robust catalysts with tunable oxygen vacancies to improve CO 2 conversion efficiency [22,58,59]. Controlling the number and distribution of oxygen vacancies enables precise regulation of the adsorption and activation of reactants during CO 2 conversion.…”
Section: Catalytic Performance In Liquid Phasementioning
confidence: 99%
“…The Ni nanoparticles on SiO2 were larger than those on P-CeO2 and H-CeO2 with abundant OVs (Table S1). No significant Ov signals were observed for the Ni/C-CeO2, Ni/P-CeO2, and Ni/H-CeO2 catalysts because the strong signal from Ni 0 hindered the other catalysts [39,40] (Fig. S4).…”
Section: Structure Of Catalystsmentioning
confidence: 99%